Interação entre texto e imagem por meio do livro físico - PANTOJA, Monique Costa (2018)
It aims to present aspects related to the picture book. It presents the types of relationships between the text (written language) and image (visual language); firstly among itself and after inside the scope of the book. The result is the existence of proper nomenclatures for this hybrid media: illustrated book, book with illustrations and comics. It was observed the existence of a remarkable public as diverse as well on these types of media. There are, however, preference to and for children's audience. It reaffirms that the book, as a product, is designed according to the target audience and due to its multiplicity, is required special attention during its building. It is concluded that the illustrated book which holds three pillars: text, image, and repository posses a huge range of possibilities about its functions and relationships; consequently, it is a complex object of study, however, is often treated as simplistic and inferior literature.